2008
DOI: 10.1002/macp.200700297
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Spin Diffusion Coefficients in Glassy Polymers: Failure of a Simple Scaling Law

Abstract: For a series of polymers, the spin diffusion coefficients D do not scale as predicted from a simple expression based on regularly spaced nuclei. We compare D for PVA and polystyrene with their side group either protonated or deuterated. For polystyrene, D is considerably reduced from 600–800 to 65 nm2 · s−1. For PVA, D is already small for the fully protonated chain and is only slightly reduced from 170 to 130 nm2 · s−1. This indicates that the rapidly rotating methyl group does not contribute appreciably to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…As we investigated local spin diffusion, it is not yet clear whether this effect is of the same importance for large-scale spin-diffusion. However, we found several studies in which spin diffusion coefficients lower than 0.8 nm 2 /ms were observed on both local [15,28] and larger [30][31][32][33] length scales. In addition, spin diffusion coefficients calculated on the basis of different models usually provide significantly smaller values than 0.8 nm 2 /ms [5,34].…”
Section: Discussion Of Literature Datamentioning
confidence: 85%
“…As we investigated local spin diffusion, it is not yet clear whether this effect is of the same importance for large-scale spin-diffusion. However, we found several studies in which spin diffusion coefficients lower than 0.8 nm 2 /ms were observed on both local [15,28] and larger [30][31][32][33] length scales. In addition, spin diffusion coefficients calculated on the basis of different models usually provide significantly smaller values than 0.8 nm 2 /ms [5,34].…”
Section: Discussion Of Literature Datamentioning
confidence: 85%
“…19 This value was in turn also used as a basis for the calibration of the SD coefficients of the mobile phase based on T 2 times according to Mellinger et al 3 There are, however, a number of works in which significantly smaller diffusion coefficients are discussed. 6,16,[21][22][23][24][25] For example, in a paper of Schmidt-Rohr and coworkers, 22 local SD processes were investigated on a scale of approximately 1 nm, and a local SD coefficient in glassy PS of approximately 0.2 nm 2 ms À1 was derived. This observation was recently confirmed for other systems by Roos et al 25 Vanderhart and McFadden 23 suggested SD coefficients for PS on the order of 0.6 nm 2 ms À1 .…”
Section: Reevaluation Of the Sd Coefficientsmentioning
confidence: 99%
“…2,[6][7] The diffusion of molecular species into polymer matrices is usually measured on bulky materials via gravimetry and pressure decay methods 8 or by techniques based on refractive index variations. 9 Conversely, when small polymer masses are involved, dedicated expensive and time consuming laboratory techniques such as nuclear magnetic resonance, [10][11] infrared spectroscopy, 12 and neutron reflectometry 13 are frequently needed. Some attempts to measure diffusivity in thin films via UV-Vis spectroscopy have been done using chromophore analytes, 14 but the use of these colored compounds aims to detect opportunely labelled molecules and then, it cannot be employed for uncolored species.…”
mentioning
confidence: 99%